Strategies of Darul Muttaqin Mosque Management in Addressing The Misuse of Mosque Facilities as a Sleeping Area - Pertiwi, Khoir Annisa; Riris Raisyah Parira; Nurhaliza; Ririn Dwi Novertha; Yunita Lidyanti; Ismawati; Lisa Rosmala Dewi; Yuyun Mardiana; Lira Firna (Wardah, 2025)
The Darul Muttaqin Mosque has encountered a phenomenon that has become a concern, namely the misuse of mosque facilities, particularly the use of the mosque as a sleeping area by some students. Although the mosque's primary purpose is for worship and religious activities, the phenomenon of students sleeping in the mosque has been occurring more frequently. This study aims to explore in depth the strategies employed by the management of the Darul Muttaqin Mosque to address the misuse of mosque facilities, specifically regarding the issue of sleeping in the mosque. The research employs a qualitative method with a descriptive approach, involving in-depth interviews, observation, and documentation. The theoretical framework used is Henry Mintzberg’s (1939) Strategic Management Theory. The findings indicate that mosque management faces challenges in maintaining the sanctity and primary function of the mosque as a place of worship. The misuse of mosque facilities, particularly the use of the mosque as a sleeping area, often occurs due to a lack of ethical awareness and discipline among visitors. Although the mosque management has made efforts to reprimand visitors sleeping in inappropriate areas, these efforts often fail to yield consistent results. Therefore, a more systematic and participatory approach is needed to address this issue.